Urinary Continence Following Repair of Intermediate and High Urogenital Sinus (UGS) in CAH. Experience with 55 Cases - Bailez, Maria Marcela; Cuenca, Estela Susana; Dibenedetto, Victor (Frontiers in Pediatrics, 2014)
Aim :Evaluate postoperative urinary continence in patients withcongenital adrenal hyperplasia(CAH)with intermediate (IT)and high urogenital sinus (UGS) who underwent a UGS mobilization maneuver . Methods: We called IT to those that although needing an aggressive dissection to get to the vagina, still have enough urethra proximal to the vaginal confluence. Very low variants are excluded from this analysis. Dissection always started in the posterior wall of the UGS with an aggressive separation from the anterior rectal wall. If the wide portion of the vagina was reached dissection stopped and the UGS opened ventrally widening to the introitus. Nineteen patients were treated using this maneuver (Group1). When more dissection was required the anterior wall of the UGS was dissected and carefully freed from the low retropubic space. Then the UGS was opened either ventrally or dorsally. Thirty three patients required this approach (Group 2) .Combined procedures were used in 3 patients with high UGS (Group 3). Results : Mean age at the time of the repair and length of the UGS were 12.2 years (4 months to 18 years) and 3.75 cm (3 -8 cm)for G 1; 8 years (5 months to 17 years) and 6.34 cm ( 4-12 cm) in G2 and 8,3 years (2 -14 y) and 11.5cm (11-12cm) in G3. All patients had been regularly followed. Mean age at last follow up of 14.3y, 17y and 9.9y for groups 1, 2 and 3 respectively. All patients continue to void normally and are continent. All patients have 2 separate visible orifices in the vulva. Only 3 are sexually active. Conclusion: UGS mobilization for vaginoplasty in girls with CAH does not compromise voiding function or urinary continence,